2009
DOI: 10.1002/adfm.200900591
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of Manmade and Biopolymer Nanofibers—Progress in Techniques, Materials, and Applications

Abstract: Electrospinning of nanofibers has developed quickly from a laboratory curiosity to a highly versatile method for the preparation of a wide variety of nanofibers, which are of interest from a fundamental as well as a technical point of view. A wide variety of materials has been processed into individual nanofibers or nanofiber mats with very different morphologies. The diverse properties of these nanofibers, based on different physical, chemical, or biological behavior, mean they are of interest for different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
164
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(168 citation statements)
references
References 84 publications
(123 reference statements)
1
164
0
3
Order By: Relevance
“…A linear t for the data points from TEM analysis yielded a growth rate of 0.20 nm per cycle, where ALD should be acknowledged for the excellent control on the lm thickness against deposition cycles. 19,42,43 On the other hand, SE from Si yielded a growth rate 0.18 nm per cycle, which is closely comparable with the results from TEM. Fig.…”
Section: Resultssupporting
confidence: 83%
“…A linear t for the data points from TEM analysis yielded a growth rate of 0.20 nm per cycle, where ALD should be acknowledged for the excellent control on the lm thickness against deposition cycles. 19,42,43 On the other hand, SE from Si yielded a growth rate 0.18 nm per cycle, which is closely comparable with the results from TEM. Fig.…”
Section: Resultssupporting
confidence: 83%
“…(Agarwal, Greiner, & Wendorff, 2009;Bhardwaj & Kundu, 2010;Ramakrishna et al, 2006;Teo & Ramakrishna, 2009). Moreover, functional electrospun nanofibrous composite structures can also be produced by incorporating functional additives and/or nanoparticles in the fiber matrix or on the fiber surface (Andrew & Clarke, 2008;Anitha, Brabu, Thiruvadigal, Gopalakrishnan, & Natarajan, 2012;Dong, Wang, Sun, & Hinestroza, 2008;He, Hu, Yao, Wang, & Yu, 2009;Roso, Sundarrajan, Pliszka, Ramakrishna, & Modesti, 2008;Zhang, Shao, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Unique properties of electrospun nanofibers/nanowebs including a relatively large surface area to volume ratio and pore sizes within the nanoscale and multi-functionality due to the presence of functional additives and nanoparticles make them favorable candidates in a variety of application areas such as membranes/nanofilters, wound dressing, tissue engineering, drug delivery, nanotextiles, nanocomposites, energy, environment, etc. (Agarwal et al, 2009;Bhardwaj & Kundu, 2010;Chigome, Darko, & Torto, 2011;Lu, Wang, & Wei, 2009;Ramakrishna et al, 2006;Teo & Ramakrishna, 2009;Thavasi, Singh, & Ramakrishna, 2008;Xie, Li, & Xia, 2008;Yoon, Hsiao, & Chu, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5) it is observed that the average fiber diameter decreases with the increase in manganese acetate concentration. This is mostly due to the increase in electrical conductivity of the solution with increasing salt concentration [22]. SEM photograph of the calcined nanofiber at 1000 ℃ (Fig.…”
Section: Morphology Study Of Manganese Acetate + Pva Composite Nanomentioning
confidence: 99%